2017
DOI: 10.1055/s-0043-118912
|View full text |Cite
|
Sign up to set email alerts
|

Liquid and Vapor-Phase Activity of Artemisia annua Essential Oil against Pathogenic Malassezia spp.

Abstract: essential oil has given us many encouraging results for its numerous antimicrobial properties. In this study, the essential oil, both in liquid and in vapor phases, was tested against various species closely related to many skin disorders in humans and animals. treatment and eradication are mainly based on old azole drugs, which are characterized by poor compliance, unpredictable clinical efficacy, emerging resistance, and several side effects. Monoterpenes (ca. 88%) represent the most abundant group of compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…Artemisia annua EO had volatile activity against Malassezia spp. ; MICs were lower than those obtained in liquid phase [70].…”
Section: Discussioncontrasting
confidence: 63%
“…Artemisia annua EO had volatile activity against Malassezia spp. ; MICs were lower than those obtained in liquid phase [70].…”
Section: Discussioncontrasting
confidence: 63%
“…Before the introduction to practical use of new preparations based on VAs, a detailed evaluation of their efficiency and safety is necessary, whereas in vitro screening is usually the first step in this process. Among in vitro techniques, vapour phase tests demonstrate the antimicrobial activity of VAs in a way which respects their specific physicochemical properties such as high volatility, Candida dubliniensis IZ 8.5 cm for 0.32-0.64 µL/cm 3 of EO [89] Candida glabrata IZ 8.5 cm for 0.32-0.64 µL/cm 3 of EO [89] Candida krusei IZ 8.5 cm for 0.32-0.64 µL/cm 3 of EO [89] Candida norvegensis IZ 8.5 cm for 0.32-0.64 µL/cm 3 of EO [89] Candida parapsilosis IZ 4.4-8.5 cm for 0.32-0.64 µL/cm 3 of EO [89] Candida tropicalis IZ 6.8-8.5 cm for 0.32-0.64 µL/cm 3 of EO [89] Malassezia furfur O 100 % for 0.133-0.530 µL/cm of air [90] Malassezia globosa O 100 % for 0.066-0.133 µL/cm of air [90] Malassezia pachydermatis O 100 % for 0.066 µL/cm 3 of air [90] Malassezia sloffiae O 100 % for 0.066-0.530 µL/cm of air [90] Malassezia sympodialis O 100 % for 0.133-0.530 µL/cm of air [90] Artemisia nilagirica…”
Section: Methods For Evaluation Of Growth Inhibitory Effects Of the Vmentioning
confidence: 99%
“…Therefore, it is necessary to sufficiently investigate the composition and properties of the vapors of essential oil. Currently, several researchers have investigated the vapor phase of the essential oil, but it deserves much wider research and consideration when examining the properties of essential oils [6][7][8][9][10][11][12]. It is assumed that active compounds in both phases are synergic and furthermore it has been shown that vapor phase is sometimes even more effective than liquid phase to some microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, several methods and the modification-testing MICs of antimicrobials in the vapor phase were developed. Usually, the disc volatilization method with various modifications is used [10][11][12]17,18].…”
Section: Introductionmentioning
confidence: 99%